2008
DOI: 10.4161/cbt.7.1.5134
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of retinoic acid treatment in bladder cancer: Impact on recurrence, survival and TGFα and VEGF as end-point biomarkers.

Abstract: Introduction and aims: Being best-studied superficial bladder cancer (SBC) chemopreventives, retinoids' negative studies and toxicity were stumbling. With proper understanding of retinoid metabolism, we aimed at investigating combined ketoconazole (a strong inhibitor of retinoic acid-catabolizing cytochrome P450s) all-trans retinoic acid (Keto-atRA) SBC treatment. VEGF and TGFα levels are end-point pathogenetic biomarkers involved in early SBC.Results: Keto-atRA treatment significantly improved survival time a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 71 publications
0
25
0
Order By: Relevance
“…ILC2 that produce IL-13 (67); and (c) a meta-analysis showed that vitamin A plays a protective role in BCa (68), and ATRA treatment was found to significantly improve survival and recurrence rates in NMIBC patients (69). Furthermore, a combination of depletion or attenuation of MDSCs and concomitant stimulation of effector T cells may be of interest.…”
Section: Discussionmentioning
confidence: 99%
“…ILC2 that produce IL-13 (67); and (c) a meta-analysis showed that vitamin A plays a protective role in BCa (68), and ATRA treatment was found to significantly improve survival and recurrence rates in NMIBC patients (69). Furthermore, a combination of depletion or attenuation of MDSCs and concomitant stimulation of effector T cells may be of interest.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, CRBP1 down-regulation promoted the progression of tumors through the inhibition of RA receptor activity (24). In terms of BC, RA treatment effectively reduced the recurrence rate and increased the survival time of superficial BC patients (26,27). However, there have been no gain-of-function studies on the CRBP1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Results for these trials were mixed, with some showing significant preventative effects (Alfthan et al, 1983;Studer et al, 1995;Yoshida et al, 1986) and others showing less promising results (Decensi et al, 2000;Prout & Barton, 1992). Mild to severe toxicities were also noted in many of these studies and may potentially limit vitamin A's use as a chemopreventive agent (Hameed & el-Metwally, 2008). More recently, to enable lower doses of retinoic acids and decrease unwanted side effects, combinations of retinoic acid and inhibitors of the CYP26A enzyme (involved in degradation of vitamin A) have been explored with some success (Hameed & el-Metwally, 2008).…”
Section: Vitamin Amentioning
confidence: 99%
“…Mild to severe toxicities were also noted in many of these studies and may potentially limit vitamin A's use as a chemopreventive agent (Hameed & el-Metwally, 2008). More recently, to enable lower doses of retinoic acids and decrease unwanted side effects, combinations of retinoic acid and inhibitors of the CYP26A enzyme (involved in degradation of vitamin A) have been explored with some success (Hameed & el-Metwally, 2008). Although a recent cohort study showed no significant association of several vitamins including retinoids with urothelial carcinoma risk (Hotaling et al, 2011), other past studies provide some compelling evidence for vitamin A's efficacy.…”
Section: Vitamin Amentioning
confidence: 99%
See 1 more Smart Citation